The Use of Proton-Transfer-Reaction Time-of-Flight Mass Spectrometry (PTR-ToF-MS) to Determine the Volatile Organic Compounds (VOCs) Produced by Different Lactic Acid Bacterial Strains Growing in Defined Media - Sarathadevi Rajendran; Iuliia Khomenko; Patrick Silcock; Emanuela Betta; Franco Biasioli; Phil Bremer (Applied Microbiology)
Lactic acid bacteria (LAB) fermentation has been claimed as an effective way of modifying the sensory properties of plant-based foods. However, not much has been published on the influence of different LAB strains on the flavour of the volatile organic compounds (VOCs) produced. Using a defined medium (DM) and proton-transfer-reaction time-of-flight mass spectrometry (PTR-ToF-MS), we assessed the VOCs produced by seven LAB strains, Levilactobacillus brevis WLP672 (LB672), Lactobacillus delbrueckii WLP677 (LD677), Pediococcus damnosus WLP661 (PD661), Lactiplantibacillus plantarum LP100 (LP100), Pediococcus pentosaceus PP100 (PP100), Pediococcus damnosus 5733 (PD5733), and Lentilactobacillus buchneri 5335 (LU5335), at three time points during fermentation (0, 7, and 14 days) at either 25 or 35 °C. Significant variations in VOC production were observed among LAB strains, growing in the same DM composition at either 25 °C or 35 °C. Specifically, the concentration of m/z 87.043 (t.i. diacetyl) was significantly (p < 0.05) higher at 7 days of fermentation at 35 °C by LP100, followed by PP100 at 35 °C and PD661 at 25 °C compared to the other strains at either 25 or 35 °C. The concentration of m/z 115.112 (t.i. 2-heptanone) was significantly (p < 0.05) higher at 7 days of fermentation at either 25 or 35 °C by LP100 compared to the other strains at all temperature and time points. The concentration of m/z 49.011 (t.i. methanethiol) was significantly (p < 0.05) higher after 7 days of fermentation at 35 °C by LB672 compared to the other strains at either 25 or 35 °C. The concentration of m/z 71.085 (t.i. 3-methyl butanol) was significantly (p < 0.05) higher after 7 days of fermentation at either 25 or 35 °C by PD661, LU5335, or PD5733 compared to the other strains studied. A notable increase in specific VOC concentrations was observed at 35 °C compared to 25 °C. This research demonstrates that LAB strains generate distinct VOC profiles in a DM based on strains and fermentation conditions. Therefore, this knowledge provides a basis for controlling and enhancing flavour in plant-based fermentations.